PERLINDUNGAN HUKUM DALAM JUAL BELI TANAH DI BAWAH TANGAN BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA - K. Hendra Mahesa; Muhamad Jodi Setianto; Komang Febrinayanti Dantes (Jurnal Ilmu Hukum Sui Generis, 2023)
The purpose of this research is to recognize and assess the legal safeguards available to purchasers engaged in clandestine transactions of land rights. Additionally, it aims to scrutinize the legal ramifications that buyers face when participating in such under-the-table transactions under the framework of Law No. 5 of 1960 concerning Fundamental Agrarian Regulations. This study employs a normative juridical research approach, which seeks to establish legal truths based on normative aspects, primarily due to normative gaps. The research methodology is characterized as analytical-descriptive, designed to provide an overview of how regulations are implemented based on the currently applicable legal provisions. The process of collecting legal materials utilizes a legal materials inventory. The findings of this research indicate that legal protection for purchasers involved in clandestine land rights transactions persists in both a preventative and repressive manner. Preventative legal safeguards are grounded in the stipulations outlined in Article 1491 of the Civil Code, while repressive legal safeguards manifest as law enforcement measures encompassing a range of sanctions, including fines, compensatory measures, imprisonment, additional penalties, and other methods. The legal consequences stemming from these transactions include the inability of buyers to register the transfer of land rights or initiate the name-change process on certificates at the Local Land Office. Additionally, buyers lack substantial evidentiary support in the event of disputes or other legal issues arising regarding the land they have purchased. Furthermore, buyers are unable to independently secure certificates as collateral to obtain credit, as this process necessitates the involvement of the land seller in question.